Limited evidence of coupling between above and belowground functional traits in tropical dry forest seedlings - Arrieta-González, Rosa (2021)
Introduction: Water availability is one of the main factors determining the distribution of woody species in the tropics. Although the functional mechanisms that determine the species tolerance to water deficit have been extensively studied in adult individuals, the responses of early ontogenetic stages have been less explored. Objective: To identify functional strategies and trait correlations between different seedlings' dimensions (leaf, stem, and root). We expect limited coordination between above and below-ground functional traits due to a single conservation-acquisition trade-off cannot capture the variability of functions and environmental pressures to which the root system is subjected. Methods: We measured 12 functional traits belonging to 38 seedling species in a tropical dry forest in Colombia. We explored the relationships between pairs of traits using Pearson correlations, and to obtain an integrated view of the functional traits, a principal component analysis (PCA) was performed. Results: The results showed limited evidence of linkage between above- and below-ground traits, but we did find significant correlations between traits for the continuum of conservative and acquisitive strategies. Root traits related to water and nutrient take capacity formed an orthogonal axis to the acquisitive-conservative continuum. Conclusions: Our results showed that dry forest seedlings have different functional strategies to cope with water deficit. The incorporation of root traits helps to explain new functional strategies not reported for leaf and stem traits. This study contributes to understanding the mechanisms that explain species coexistence and is particularly relevant for predicting future forest trajectories.